P152 The association between adult height, socioeconomic status and idiopathic pulmonary fibrosis: a population based case-control study. (15th November 2017) - Glover, T; Hutchinson, JP; McKeever, T; Hubbard, RB; Navaratnam, V
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is an increasingly important public health issue worldwide, but the underlying aetiology is still unknown. The aim of this study was to investigate whether adult height or socioeconomic status are associated with the lifetime risk of developing IPF. Methods: We used data from The Health Improvement Network (THIN), an electronic longitudinal UK primary care database to conduct a matched case-control study to investigate if adult height and socioeconomic status are associated with IPF. Incident cases of IPF were identified using previously published Read Codes. General population controls were identified as a 4:1 incident density sample, matched by age, gender and general practice. Our exposures were adult height and socio-economic index as measured by Townsend Index recorded before the date of diagnosis. We used conditional logistic regression to estimate odds ratios for the associations between each exposure and IPF. Adult height was modelled as quintiles and as a continuous variable. Results: The final study population consisted of 1699 incident cases of IPF and 5339 matched general population controls. Mean age of cases was 74.6 years (Standard Deviation [SD] 9.6) and 64.2% were male. Mean height in men and women were 1.73 (SD 0.07) and 1.59 (SD 0.6) metres respectively. There was no association between adult height quintiles and IPF after adjusting for socio-economic status (see Table 1 ). However, when modelled as a continuous variable, we found a weak inverse association between every metre increase in adult height and IPF, after controlling for socio-economic status. (OR 0.46, 95% CI 0.19–1.07; p=0.07). There was also strong evidence of effect modification between adult height and sex (p=0.03), such that the effect of increasing height quintile was stronger in women (OR 0.93, 95% CI 0.87 to 0.99) and weaker in men (OR 0.99, 95% CI 0.94 to 1.04). We found no association between socio-economic status and IPF (see Table 1 ). Conclusions: Our findings raise the possibility that early life exposures may influence the lifetime risk of developing idiopathic pulmonary fibrosis. We also demonstrated that unlike many respiratory diseases, IPF is spread evenly through all sections of society.